Winding pathways to rural regeneration : exploring challenges and success factors for three types of rural changemakers in the context of knowledge transfer and networks - Janc, Krzysztof; Dołzbłasz, Sylwia; Raczyk, Andrzej; Skrzypczyński, Robert (MDPI, 2023)
The regeneration of rural areas is a multifaceted process driven by a variety of actors operating in diverse contexts. Understanding specific barriers faced by these actors—as well as factors that contribute to the success of their initiatives—therefore seems to be a prerequisite for designing policies that can effectively support rural changemakers and thus promote rural regeneration. The goal of this exploratory paper is to identify key challenges and success factors for three types of rural changemakers—rural newcomers, new entrants into farming, and farming successors—based on empirical data gathered in three case studies conducted as part of the Horizon2020 project “RURALIZATION” in Poland in 2021. The results of the study show that one of the most important determinants of the success of rural changemakers’ activities is having adequate formal and informal knowledge. This is important in the context of knowledge transfer, interacting with and functioning in the local environment, and consequently laying the foundations for rural regeneration. Rural regeneration must be treated as a complex and long-term process that is strongly linked to the activation of knowledge transfer mechanisms.
Keywords: rural regeneration; rural changemakers; knowledge; local communities